PENGARUH SOSIAL MEDIA PEMASARAN INSTAGRAM DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN - Shoffa Ayuna Tamama; Tatag Herbayu (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research was conducted with the aim to determine the effect of social media marketing and product quality on buying decisions at Es Teh Indonesia Franchise Jatiwaringin. The type of the research used in this research is purposive sampling. The sample used in this study is Collage student have transacted in Es Teh Indonesia Franchise Jatiwaringin using the sampling technique and using a data collection method using questioner. The data analys technique in this study used multiple linear regression. Based on the result of this study, social media marketing have a positive and significant effect on buying decisions. Product quality has a positive and significant effect on buying decisions. Social media marketing and product quality a positive and significant effect on buying decision.